Integrated risk management : a mechanism to minimise risks for local government : a critical perspective - Geldenhuys, L. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (School of Public Management and Planning ))—University of Stellenbosch, 2006.